A predictive reliability assessment model for transmission systems using tie-sets evaluation technique - Domingo, Redel M (2006)
Electric utilities traditionally rely on deterministic approach to guide transmission planning which runs the risk of over or under investment and its essential weakness is not accounting for the probabilistic nature of power system behavior and equipment failures. Since system behavior is stochastic in nature, it is logical to model and assess the transmission system based on probabilistic technique. This study developed a method to predict the reliability performance of transmission systems using the Tie-Sets Evaluation Technique. The effectiveness and accuracy of the proposed approach was tested on three existing 115KV Sub-transmission Selectors of Manila Electric Company (MERALCO) with different system configurations. The reliability network model and basic reliability parameters such as failure rates, repair rates and probability of failure and success of the transmission systems and basic components were constructed. To simplify the execution of the approach, Matrix Multiplication Technique is used in deducing tie-sets and the algorithm for both techniques were automated in Matlab Program. The study made it possible to predict the future performance of transmission systems and quantify the impact to reliability of any transmission system recognition which is useful in conducting cost-benefit analysis.